A Comparative Analysis of the Medina Charter and Bhinneka Tunggal Ika in Upholding Indonesia’s National Unity: A Hadith Perspective - Rahman; Siti Nuri Nurhaidah; Mudrikatul Arafah; Miftahussa’adah Wardi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
In a pluralistic society, the primary challenge lies in fostering harmony among diverse religious and cultural groups. This study aims to explore the relevance of the Medina Charter in the context of Bhinneka Tunggal Ika (Unity in Diversity) as an effort to strengthen religious moderation in Indonesia. The research employs a literature review method, analyzing various sources related to the Medina Charter and the philosophy of Bhinneka Tunggal Ika. The findings reveal a congruence between the principles of the Medina Charter and Bhinneka Tunggal Ika, particularly in terms of recognizing diversity and providing mechanisms to manage differences for the sake of social stability. These results suggest that Islam offers a comprehensive framework for managing pluralism, which can serve as a foundation for efforts to strengthen religious moderation in Indonesia